Efficient biodegradation of malachite green by an artificial enzyme designed in myoglobin. Issue 26 (30th April 2021) - Xiang, Heng-Fang; Xu, Jia-Kun; Liu, Jiao; Yang, Xin-Zhi; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu
Abstract : An artificial enzyme of F43H/H64 myoglobin was successfully applied for efficient biodegradation of malachite green, with the catalytic efficiency exceeding those of some natural enzymes. Abstract : Synthetic dyes such as malachite green (MG) have a wide range of applications. Meanwhile, they bring great challenges for environmental security and cause potential damages to human health. Compared with traditional approaches, enzymatic catalysis is an emerging technique for wastewater treatment. As alternatives to natural enzymes, artificial enzymes have received much attention for potential applications. In previous studies, we have rationally designed artificial enzymes based on myoglobin (Mb), such as by introducing a distal histidine (F43H mutation) and creating a channel to the heme pocket (H64A mutation). We herein show that the artificial enzyme of F43H/H64A Mb can be successfully applied for efficient biodegradation of MG under weak acid conditions. The degradation efficiency is much higher than those of natural enzymes, such as dye-decolorizing peroxidase and laccase (13–18-fold). The interaction of MG and F43H/H64A Mb was investigated by using both experimental and molecular docking studies, and the biodegradation products of MG were also revealed by UPLC-ESI-MS analysis. Based on these results, we proposed a plausible biodegradation mechanism of MG. With the high-yield of overexpression in E. coli cells, this study suggests that the artificial enzyme has potential applications in the biodegradation of MG in fisheries and textile industries.